Jiajiejian gel ameliorates thyroid nodules through regulation of thyroid hormones and suppression of the (IL-6, TNF-α, IL-1β)/JAK2/STAT3/VEGF pathway - Changlin Wang; Changlin Wang; Xiangju Gao; Mingqi Qiao; Dongmei Gao; Yinghui Guo; Jieqiong Wang; Chunhong Song (Frontiers Media S.A., 2024)
BackgroundThe high incidence of thyroid nodules and their rapid growth in recent years have become an important issue affecting public health. Traditional Chinese medicine (TCM) external treatments have unique advantages in treating this disease, but the currently available external preparations are relatively few and the therapeutic mechanism is unclear. Jiajiejian gel (JJJG) is a TCM external preparation developed by our team for the thyroid nodule treatment, which has been preliminarily proven to be safe and effective in clinical practice.ObjectiveThe current study was aimed to elucidate the therapeutic effects and the underlying mechanisms of JJJG on thyroid nodules in rats.MethodsThe contents of paeonol and forsythoside A in JJJG were determined by HPLC. The thyroid nodules rat model was established through oral gavage of 0.1% propylthiouracil (PTU) for 6 weeks and meanwhile the rats were treated with external JJJG (0.26, 0.52, 1.04 g/kg). Subsequently, the therapeutic effect of JJJG was observed by means of ultrasonic examination, morphology observation, organ coefficients determination and histopathological analysis. Mechanismlly, the levels of FT3, FT4 and TSH in serum were measured and transcriptomics methods were used to analyse and screen the key targets and pathways of alleviating thyroid nodules by JJJG. Further, gene and protein expression levels of key factors in the pathways were measured and validated using quantitative real-time PCR, ELISA, western blotting and immunofluorescence, so as to clarify the therapeutic mechanism.ResultsThe contents of the paeonol and forsythoside A were 1.160 and 0.608 mg/g, respectively. JJJG reduced thyroid swelling, improved nodular lesions, decreased thyroid coefficients, and inhibited abnormal nodular hyperplasia of follicular epithelial cells. In terms of mechanism, JJJG significantly increased the levels of FT3 and FT4 and decreased TSH level in serum (P < 0.05). Transcriptomics suggested that the (IL-6, TNF-α, IL-1β)/JAK2/STAT3/VEGF pathway may be one of the key mechanisms in the treatment of thyroid nodules by JJJG. Further validation experiments demonstrated that JJJG significantly reduced the mRNA expression and protein content of IL-1β, IL-6 and TNF-α in thyroid tissue, as well as the mRNA expression of JAK2, STAT3 and VEGF and the protein expression of p-JAK2/JAK2, p-STAT3/STAT3 and VEGF (P < 0.05).ConclusionThis study indicates that JJJG efficiently ameliorates thyroid nodules by regulating the levels of FT3, FT4 and TSH in serum and suppressing (IL-6, TNF-α, IL-1β)/JAK2/STAT3/VEGF pathway in thyroid tissue, providing a potential therapeutic approach for thyroid nodules.